Candesartan Has No Clinically Meaningful Effect on the Plasma Concentrations of Cytochrome P450 2C8 Substrate Repaglinide in Humans - Piha, Mikael O. W.; Cajanus, Kristiina; Engström, Marica T.; Neuvonen, Mikko; Bergmann, Troels K.; Niemi, Mikko; Backman, Janne T.; Filppula, Anne M.; Tornio, Aleksi (American Society for Pharmacology & Experimental Therapeutics (ASPET), 2025)
In vitro evidence shows that the acyl-β-D-glucuronide metabolite of candesartan inhibits cytochrome P450 (CYP) 2C8 with an inhibition constant of 7.12 μM. We investigated the effect of candesartan on the plasma concentrations and glucose-lowering effect of repaglinide, a sensitive clinical CYP2C8 index substrate. In a randomized crossover study, ten healthy volunteers ingested 8 mg of candesartan or placebo daily for three days, and on day 3, they also ingested 0.25 mg of repaglinide one hour after candesartan or placebo. We measured the plasma concentrations of repaglinide, candesartan, and candesartan acyl-β-D-glucuronide, and blood glucose concentrations for up to nine hours after repaglinide intake. Candesartan had no effect on the area under the plasma concentration-time curve and peak plasma concentration of repaglinide compared with placebo, with ratios of geometric means of 1.02 [P = 0.809; 90% confidence interval (CI) 0.90–1.15] and 1.13 (P = 0.346; 90% CI 0.90–1.43), respectively. Other pharmacokinetic variables and blood glucose concentrations were neither affected. Candesartan acyl-β-D-glucuronide was detectable in seven subjects, in whom the peak concentration of repaglinide was 1.32-fold higher in the candesartan phase than in the placebo phase (P = 0.041; 90% CI 1.07–1.62). Systemic concentrations of candesartan acyl-β-D-glucuronide were very low compared with its CYP2C8 inhibition constant (ratio ≪ 0.1). Furthermore, in a cohort of 93 cancer patients, no indication of decreased paclitaxel clearance was found in four patients using candesartan concomitantly. In conclusion, candesartan therapy is unlikely to inhibit CYP2C8-mediated metabolism of other drugs to any clinically significant extent.